IDENTIFIKASI KEBUTUHAN DAN DESAIN MEDIA WORDWALL INTERAKTIF UNTUK MATERI KESEBANGUNAN DI SMP KELAS IX - Tnesi, Stiven Aloysius; Mau, Elfrida Olo; Jomar, Guido Stefano; Lakapu, Meryani; Jagom, Yohanes Ovaritus (Universitas Batanghari Jambi, 2025)
This study aims to analyze the needs and design Wordwall-based interactive learning media on sereviation materials for junior high school students in grade IX. This research is the initial part of development research (R&D) with the IDDIE model which is focused on the Identify and Design stages. The analysis stage was carried out through classroom observation and interviews with teachers, which showed that students had difficulty in understanding the concept of awakening due to its abstract nature and lack of interesting learning media. Based on the results of the analysis, an interactive learning media in the form of a Wordwall quiz was designed with a variety of questions and visuals that suit the characteristics of the students. The design includes mapping basic competencies, material preparation, and visual and interactive media design. The results of the design stage result in an initial prototype of the media that is ready to be validated at the next stage of development. This media is expected to be an innovative solution in supporting contextual and fun mathematics learning